LAND USE CHANGES IN POST-SOCIALIST ROMANIA. CASE STUDY: BISTRIȚA VALLEY, NEAMȚ COUNTY - BÎRSĂNUC, Elena-Manuela (Studia Universitatis Babeș-Bolyai Geographia, 2019)
Land use and vegetation density are by far a major feature of post-socialist Romania. Free access to Landsat imagery archive makes it possible to track these changes in time and link them to their causes and other factors that facilitated the changing process, like political shifts, social trends and economic decisions. After 1989, the Romanian forests entered the restitution period marked by three laws (1991, 2000 and 2005) which has inevitably led to major changes in land usage by modifying the ownership and power of decision. Using tools like vegetation indexes and supervised classifications, the analysis is focused on highlighting the link between socio-political decisions and their impact on land use by analyzing the rural area of Bistrița Valley, Neamț County through the years of 1985-2017. Therefore, the study demonstrates the connection of institutional decisions to the natural environment, it explains the reasons behind land use changes and also formulates future perspectives for forest recovery process in this area.